Prostatic Arterial Embolization to Treat Benign Prostatic Hyperplasia - Pisco, JM (2011)
PURPOSE: To evaluate whether prostatic arterial embolization (PAE) might be a feasible procedure to treat lower urinary tract symptoms associated with benign prostatic hyperplasia (BPH). MATERIALS AND METHODS: Fifteen patients (age range, 62-82 years; mean age, 74.1 y) with symptomatic BPH after failure of medical treatment were selected for PAE with nonspherical 200-μm polyvinyl alcohol particles. The procedure was performed by a single femoral approach. Technical success was considered when selective prostatic arterial catheterization and embolization was achieved on at least one pelvic side. RESULTS: PAE was technically successful in 14 of the 15 patients (93.3%). There was a mean follow-up of 7.9 months (range, 3-12 months). International Prostate Symptom Score decreased a mean of 6.5 points (P = .005), quality of life improved 1.14 points (P = .065), International Index of Erectile Function increased 1.7 points (P = .063), and peak urinary flow increased 3.85 mL/sec (P = .015). There was a mean prostate-specific antigen reduction of 2.27 ng/mL (P = .072) and a mean prostate volume decrease of 26.5 mL (P = .0001) by ultrasound and 28.9 mL (P = .008) by magnetic resonance imaging. There was one major complication (a 1.5-cm(2) ischemic area of the bladder wall) and four clinical failures (28.6%). CONCLUSIONS: In this small group of patients, PAE was a feasible procedure, with preliminary results and short-term follow-up suggesting good symptom control without sexual dysfunction in suitable candidates, associated with a reduction in prostate volume.